Copper paste for forming sintered copper pillars and method for producing joint body

JP7651832B2Active Publication Date: 2025-03-27RESONAC CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2020167122
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-01
Publication Date
2025-03-27
Estimated Expiration
2040-10-01

AI Technical Summary

Benefits of technology

【0020】 本発明によれば、焼結性及び接合性に優れる、焼結銅ピラー形成用銅ペーストを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651832000003
    Figure 0007651832000003
  • Figure 0007651832000004
    Figure 0007651832000004
  • Figure 0007651832000005
    Figure 0007651832000005
Patent Text Reader

Abstract

To provide a copper paste for forming a sintered copper pillar having excellent sinterability and bondability.SOLUTION: A copper paste for forming a sintered copper pillar is intended to form a sintered copper pillar for joining members together, and includes metal particles and an organic dispersant. The metal particles includes copper particles. The organic dispersant includes an amount of exceeding 99 mass% of a high boiling point dispersant whose boiling point is 280°C or above on the basis of a total mass of the organic dispersant, and also includes a low setting point dispersant whose setting point is 20°C or below.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a copper paste for forming a sintered copper pillar and a method for producing a bonded body. [Background technology]

[0002] Solder joints are generally used for electrical joints in electronic devices. For example, in flip-chip joints of microdevices, solder balls or solder paste are used to join the microdevice to electrode pads on a substrate.

[0003] In recent years, in flip-chip bonding, as the pitch of terminals becomes narrower, a method has been used in which metal pillars are formed on microdevices and the metal pillars are soldered to electrode pads on a substrate. However, solder bonding has problems such as (1) Kirkendall voids occurring between the solder and the electrode pads and between the solder and the metal pillars, (2) when a reflow process is performed again after bonding, the solder melts and causes bonding failure, and (3) signal reflection occurs due to impedance mismatch at the interface between different metals.

[0004] In response to this, methods of bonding using metals other than solder are being considered. For example, the following Patent Document 1 proposes a method of bonding between a copper pillar provided on a microdevice and a copper pad on a substrate using a bonding agent (copper paste) containing a mixture of copper microparticles and copper nanoparticles. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] US Patent Application Publication No. 2016 / 0351529 Summary of the Invention [Problem to be solved by the invention]

[0006] The method of Patent Document 1 requires the formation of copper pillars on the device in advance, but the mainstream copper pillar formation method, electrolytic plating, has the problem that it takes time to form the pillars. Another problem is that increasing the plating speed results in large variations in height.

[0007] Therefore, the present inventors have been studying a method of forming a sintered copper pillar and bonding the bonding members together by forming a pillar precursor between bonding members using a copper paste containing copper particles and an organic dispersion medium and sintering the pillar precursor. This method makes it possible to form a sintered copper pillar efficiently and accurately. The copper paste used to form such a sintered copper pillar (copper paste for forming a sintered copper pillar) is required to have excellent bonding properties and excellent sintering properties.

[0008] Therefore, an object of the present invention is to provide a copper paste for forming a sintered copper pillar, which has excellent sinterability and bondability. [Means for solving the problem]

[0009] The present inventors have found that the sinterability and bondability of the copper paste are improved by using a high-boiling organic dispersion medium having a boiling point equal to or higher than a specific temperature as an organic dispersant contained in the copper paste. In addition, since copper paste is usually printed at room temperature (e.g., 25°C), it was thought that the physical properties (e.g., solidification point) of the organic dispersion medium used in the copper paste at temperatures lower than room temperature would not affect the sinterability and bondability of the sintered copper pillar. However, as a result of the inventors' investigations, it was surprisingly found that when such a high-boiling organic dispersion medium is used, the physical properties at temperatures below room temperature affect the sinterability and bondability of the copper paste, and the present invention was completed.

[0010] One aspect of the present invention relates to a copper paste for forming a sintered copper pillar that joins components together, the copper paste comprising metal particles and an organic dispersion medium, the metal particles including copper particles, the organic dispersion medium including a high-boiling-point dispersion medium having a boiling point of 280°C or higher in a proportion of more than 99 mass% based on the total mass of the organic dispersion medium, and a low-freezing-point dispersion medium having a freezing point of 20°C or lower.

[0011] The copper paste for forming a sintered copper pillar of the above aspect has excellent sinterability and bondability. That is, according to the copper paste for forming a sintered copper pillar of the above aspect, it is possible to suppress the occurrence of peeling at the interface between the sintered copper pillar and the joining member while suppressing the occurrence of voids and cracks in the sintered copper pillar. Although the reason why the above effect is obtained is unclear, it is presumed that the above effect is obtained due to the fact that the proportion of the high boiling point dispersion medium in the organic dispersion medium is more than 99 mass %, which suppresses rapid volatilization of the solvent during sintering, and the low freezing point dispersion medium suppresses the solidification of the copper paste at room temperature, stabilizing the viscosity of the copper paste, and improving the printability of the copper paste.

[0012] In one embodiment, the content of the organic dispersion medium may be 1 to 20 mass % based on the total mass of the copper paste.

[0013] In one embodiment, the content of the low freezing point dispersion medium may be 50% by mass or more based on the total mass of the organic dispersion medium.

[0014] In one embodiment, the metal particles may contain sub-micro copper particles having a volume average particle size of 0.01 μm or more and less than 0.8 μm in a proportion of 30 to 100 mass % based on the total mass of the metal particles.

[0015] In one embodiment, the metal particles may contain micro copper particles having a volume average particle size of 0.8 μm or more and 50 μm or less in a proportion of more than 0 mass % and not more than 70 mass % based on the total mass of the metal particles.

[0016] In one embodiment, the low-freezing-point dispersion medium may include an organic dispersion medium having a freezing point of 10 to 20°C.

[0017] In one embodiment, the organic dispersion medium may include at least one selected from the group consisting of 2-ethylhexyl stearate, isotridecyl stearate, isobornylcyclohexanol, and octyl octanoate.

[0018] One aspect of the present invention relates to a method for producing a bonded body comprising a first member, a second member, and a sintered copper pillar joining the first member and the second member, the method comprising the steps of forming a copper paste for the side surface of the first member into a pillar shape, mounting the second member, and providing a pillar precursor between the first member and the second member, and forming a sintered copper pillar by sintering the pillar precursor.

[0019] According to the manufacturing method of the bonded body of the above aspect, a bonded body can be obtained in which peeling at the interface between the sintered copper pillar and the bonding member is reduced while suppressing the occurrence of voids, cracks, etc. in the sintered copper pillar. Effect of the Invention

[0020] According to the present invention, a copper paste for forming a sintered copper pillar having excellent sinterability and bondability can be provided. [Brief description of the drawings]

[0021] [Figure 1] 1 is a schematic cross-sectional view showing one embodiment of a bonded body according to the present invention. [Diagram 2] 1 is a schematic cross-sectional view illustrating one embodiment of a method for producing a bonded body according to the present invention. [Diagram 3] 1 is a schematic cross-sectional view illustrating one embodiment of a method for producing a bonded body according to the present invention. [Figure 4] FIG. 4 is a schematic cross-sectional view showing another embodiment of a bonded body according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Hereinafter, the embodiments for carrying out the present invention will be described in detail. However, the present invention is not limited to the following embodiments. In the following embodiments, the components (including element steps, etc.) are not essential unless otherwise specified or considered to be obviously essential in principle. The same applies to the numerical values ​​and their ranges, and they do not limit the present invention.

[0023] In this specification, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes, as long as the purpose of the process is achieved. In this specification, a numerical range indicated using "to" indicates a range including the numerical values ​​before and after "to" as the minimum and maximum values, respectively. In this specification, the content of each component in a composition means the total amount of the multiple substances present in the composition when multiple substances corresponding to each component are present in the composition, unless otherwise specified. In this specification, "boiling point" and "freezing point" mean the boiling point and freezing point at 1 atmosphere.

[0024] <Copper paste> The copper paste of one embodiment contains metal particles and an organic dispersion medium. The metal particles include copper particles. The organic dispersion medium contains an organic dispersion medium having a boiling point of 280° C. or higher (high boiling point dispersion medium) at a ratio of more than 99 mass % based on the total mass of the organic dispersion medium, and also contains an organic dispersion medium having a freezing point of 20° C. or lower (low freezing point dispersion medium).

[0025] The copper paste is a copper paste for forming a sintered copper pillar for forming a sintered copper pillar that joins components together, and is specifically used for producing a bonded body including a first component, a second component, and a sintered copper pillar that joins the first component and the second component.

[0026] The copper paste has excellent sinterability and bondability, that is, the copper paste can suppress the occurrence of voids and cracks in the sintered copper pillar while suppressing the occurrence of peeling at the interface between the sintered copper pillar and the bonding members (the first member and / or the second member).

[0027] (metal particles) The metal particles include copper particles. The copper particles refer to particles containing copper as a main component, for example, particles having a copper content of 80% by mass or more. The copper content of the copper particles may be 85% by mass or more, 90% by mass, 95% by mass or more, or 99% by mass. The metal particles may further contain metal particles other than copper particles (hereinafter also referred to as "other metal particles") as necessary.

[0028] Examples of copper particles include submicro copper particles and micro copper particles. Submicro copper particles refer to copper particles having a particle size of 0.01 μm or more and less than 0.8 μm. Micro copper particles refer to copper particles having a particle size of 0.8 μm or more and 50 μm or less.

[0029] The metal particles preferably contain submicro copper particles from the viewpoint of easily ensuring sufficient bonding strength and connection reliability. From the viewpoint of further reducing volumetric shrinkage, void generation, etc., when the pillar precursor formed by the copper paste is sintered, and from the viewpoint of more easily ensuring sufficient bonding strength, the metal particles may contain submicro copper particles and micro copper particles. In particular, when the metal particles contain submicro copper particles and micro copper particle paste, and the bonding member is a micro device, the micro device tends to exhibit good die shear strength and connection reliability.

[0030] [Submicron copper particles] As the submicro copper particles, for example, copper particles having sinterability in a temperature range of 150°C or more and 300°C or less can be used. As the submicro copper particles, for example, submicro copper particles having a volume average particle size of 0.01 μm or more and less than 0.8 μm can be used. If the volume average particle size of the submicro copper particles is 0.01 μm or more, effects such as suppression of the synthesis cost of the submicro copper particles, good dispersibility, and suppression of the amount of surface treatment agent used can be easily obtained. If the volume average particle size of the submicro copper particles is less than 0.8 μm, better sinterability can be easily obtained. From the viewpoint of further achieving the above effect, the volume average particle size of the submicro copper particles may be 0.6 μm or less, 0.5 μm or less, or 0.4 μm or less. The volume average particle size of the submicro copper particles may be 0.02 μm or more, 0.05 μm or more, or 0.1 μm or more. The volume average particle size of the sub-micro copper particles may be, for example, 0.01 μm or more and 0.5 μm or less, 0.12 μm or more and less than 0.8 μm, 0.15 μm or more and less than 0.8 μm, 0.15 μm or more and 0.6 μm or less, 0.2 μm or more and 0.5 μm or less, or 0.3 μm or more and 0.45 μm or less.

[0031] In this specification, the volume average particle size means a 50% volume average particle size. When determining the volume average particle size of copper particles, the copper particles as raw material or dried copper particles obtained by removing volatile components from copper paste are dispersed in a dispersion medium using a dispersant, and the volume average particle size can be determined by a method of measuring the dispersion medium using a light scattering particle size distribution measuring device (for example, Shimadzu nanoparticle size distribution measuring device (SALD-7500nano, manufactured by Shimadzu Corporation)). When using a light scattering particle size distribution measuring device, hexane, toluene, α-terpineol, 4-methyl-1,3-dioxolan-2-one, etc. can be used as the dispersion medium.

[0032] The shape of the submicro copper particles is not particularly limited. Examples of the shape of the submicro copper particles include spherical, clumpy, needle-like, columnar, flake-like, approximately spherical, and aggregates thereof. The shape of the submicro copper particles may be spherical, approximately spherical, or flake-like from the viewpoint of dispersibility and packing, and may be spherical or approximately spherical from the viewpoint of combustibility, dispersibility, mixability with flake-like microparticles, etc. In this specification, the term "flake-like" includes flat shapes such as plate-like and scale-like.

[0033] The aspect ratio of the sub-micro copper particles may be 5 or less, or may be 3 or less, from the viewpoints of dispersibility, packing property, and mixability with flake-shaped microparticles. In this specification, the "aspect ratio of a particle" refers to the long side / thickness of a particle. The long side and thickness of a particle can be measured, for example, from an SEM image of the particle.

[0034] The submicron copper particles may be treated with a specific surface treatment agent, such as an organic acid having 2 to 18 carbon atoms (e.g., an organic acid having an alkyl group having 1 to 17 carbon atoms).Examples of organic acids having 2 to 18 carbon atoms include acetic acid, propanoic acid, butanoic acid, pentanoic acid, hexanoic acid, heptanoic acid, caprylic acid, methylheptanoic acid, ethylhexanoic acid, propylpentanoic acid, pelargonic acid, methyloctanoic acid, ethylheptanoic acid, propylhexanoic acid, capric acid, methylnonanoic acid, ethyloctanoic acid, propylheptanoic acid, butylhexanoic acid, undecanoic acid, methyldecanoic acid, ethylnonanoic acid, propyloctanoic acid, butylheptanoic acid, lauric acid, methylundecanoic acid, ethyldecanoic acid, propyl Nonanoic acid, butyl octanoic acid, pentyl heptanoic acid, tridecanoic acid, methyl dodecanoic acid, ethyl undecanoic acid, propyl decanoic acid, butyl nonanoic acid, pentyl octanoic acid, myristic acid, methyl tridecanoic acid, ethyl dodecanoic acid, propyl undecanoic acid, butyl decanoic acid, pentyl nonanoic acid, hexyl octanoic acid, pentadecanoic acid, methyl tetradecanoic acid, ethyl tridecanoic acid, propyl dodecanoic acid, butyl undecanoic acid, pentyl decanoic acid, hexyl nonanoic acid, palmitic acid, methyl pentadecanoic acid, ethyl tetradecanoic acid saturated fatty acids such as octenoic acid, propyl tridecanoic acid, butyl dodecanoic acid, pentyl undecanoic acid, hexyl decanoic acid, heptyl nonanoic acid, heptadecanoic acid, octadecanoic acid, methyl cyclohexane carboxylic acid, ethyl cyclohexane carboxylic acid, propyl cyclohexane carboxylic acid, butyl cyclohexane carboxylic acid, pentyl cyclohexane carboxylic acid, hexyl cyclohexane carboxylic acid, heptyl cyclohexane carboxylic acid, octyl cyclohexane carboxylic acid, and nonyl cyclohexane carboxylic acid; octenoic acid, nonenoic acid, etc. , methylnonenoic acid, decenoic acid, undecenoic acid, dodecenoic acid, tridecenoic acid, tetradecenoic acid, myristoleic acid, pentadecenoic acid, hexadecenoic acid, palmitoleic acid, sapienic acid, oleic acid, vaccenic acid, linoleic acid, linolenic acid, etc. unsaturated fatty acids; terephthalic acid, pyromellitic acid, o-phenoxybenzoic acid, methylbenzoic acid, ethylbenzoic acid, propylbenzoic acid, butylbenzoic acid, pentylbenzoic acid, hexylbenzoic acid, heptylbenzoic acid, octylbenzoic acid, nonylbenzoic acid, etc. aromatic carboxylic acids. The organic acids may be used alone or in combination of two or more.By combining such an organic acid with the sub-micron copper particles, it tends to be possible to achieve both the dispersibility of the sub-micron copper particles and the desorption property of the organic acid during sintering.

[0035] The amount of the surface treatment agent may be 0.07% by mass or more and 2.1% by mass or less, 0.10% by mass or more and 1.6% by mass or less, or 0.2% by mass or more and 1.1% by mass or less.

[0036] Submicron copper particles can be commercially available. Examples of commercially available products include CH-0200 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 0.36 μm), HT-14 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 0.41 μm), CT-500 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 0.72 μm), Tn-Cu100 (manufactured by Taiyo Nippon Sanso Co., Ltd., volume average particle diameter 0.12 μm) and Cu-C-40 (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle diameter 0.2 μm).

[0037] The content of the submicro copper particles may be 30% by mass or more, 40% by mass or more, 50% by mass or more, or 60% by mass or more, based on the total mass of the metal particles, from the viewpoint of easily ensuring sufficient bonding strength, and may be 100% by mass or less, 95% by mass or less, 90% by mass or less, or 80% by mass or less. From the above viewpoint, the content of the submicro copper particles may be 30 to 100% by mass, 40 to 95% by mass, 40 to 90% by mass, 50 to 95% by mass, 50 to 90% by mass, 50 to 80% by mass, 60 to 90% by mass, or 60 to 80% by mass, based on the total mass of the metal particles. When the content of the submicro copper particles is within the above range and the bonding member is a microdevice, the microdevice tends to exhibit good die shear strength and connection reliability.

[0038] The content of the sub-micro copper particles may be 20 to 95 mass%, 30 to 85 mass%, or 40 to 75 mass% based on the total mass of the copper paste, from the viewpoints of promoting sintering, achieving good connection between the first and second components, and exhibiting low-temperature sintering properties.

[0039] [Micro copper particles] As the micro copper particles, for example, micro copper particles having a volume average particle size of 0.8 μm to 50 μm can be used. From the viewpoint of easily obtaining the above-mentioned effects by combining with the sub-micro copper particles, the volume average particle size of the micro copper particles may be 0.8 μm to 20 μm, 0.8 μm to 10 μm, 2 μm to 20 μm, 2 μm to 10 μm, 3 μm to 20 μm, or 3 μm to 10 μm.

[0040] The shape of the micro copper particles is not particularly limited, but examples thereof include spherical, lump, needle, flake, approximately spherical, and aggregates thereof.

[0041] When sub-micro copper particles and micro copper particles are used in combination, the micro copper particles may include flake-shaped micro copper particles. In this case, the flake-shaped micro copper particles are oriented approximately parallel to the bonding surface in the pillar precursor, so that the volume shrinkage of the pillar precursor in the bonding surface direction during sintering can be suppressed, and it is easy to ensure sufficient bonding strength. In particular, when the bonding member is a micro device, the micro device tends to exhibit good die shear strength and connection reliability. From the viewpoint of making the above effect prominent, the aspect ratio of the flake-shaped micro copper particles is preferably 3 or more, more preferably 4 or more, and even more preferably 6 or more.

[0042] The content of the flake-shaped micro copper particles may be more than 0 mass% and not more than 70 mass%, may be 5 mass% or more and not more than 50 mass%, may be 10 mass% or more and not more than 40 mass%, or may be 20 mass% or more and not more than 40 mass%, based on the total mass of the metal particles, from the viewpoint of suppressing the variation in height of the pillar precursor while making it easier to obtain the above-mentioned effects.

[0043] In the micro copper particles, the presence or absence of treatment with a surface treatment agent is not particularly limited. From the viewpoint of dispersion stability and oxidation resistance, the micro copper particles may be treated with a surface treatment agent. The surface treatment agent may be one that is removed during bonding. Examples of such surface treatment agents include aliphatic carboxylic acids such as dodecanoic acid, palmitic acid, heptadecanoic acid, stearic acid, arachidic acid, linoleic acid, linolenic acid, and oleic acid; aromatic carboxylic acids such as terephthalic acid, pyromellitic acid, and o-phenoxybenzoic acid; aliphatic alcohols such as cetyl alcohol, stearyl alcohol, isobornylcyclohexanol, and tetraethylene glycol; aromatic alcohols such as p-phenylphenol; alkylamines such as octylamine, dodecylamine, and stearylamine; aliphatic nitriles such as stearonitrile and decanenitrile; silane coupling agents such as alkylalkoxysilanes; and polymer treatment agents such as polyethylene glycol, polyvinyl alcohol, polyvinylpyrrolidone, and silicone oligomers. The surface treatment agent may be used alone or in combination of two or more.

[0044] The micro copper particles can be commercially available. Examples of commercially available spherical or nearly spherical micro copper particles include 1050Y (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 0.81 μm), 1100Y (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 1.1 μm), 1200Y (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 2.1 μm), 1300Y (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 4.6 μm), 1400Y (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 5.5 μm), 1200YM (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 1.9 μm), 1300YM (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 3.4 μm), 1400YM (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 4.2 μm), Cu-HWQ Examples of such Cu-HWQ powders include Cu-HWQ 1.5 μm (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 1.5 μm), Cu-HWQ 1.5 μm (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 1.4 μm), Cu-HWQ 3.0 μm (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 3.0 μm), Cu-HWQ 5.0 μm (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 4.1 μm), and Cu-HWQ 10 μm (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 9.4 μm). Commercially available flake-shaped micro copper particles include, for example, MA-C025KFD (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 7.5 μm), 4L3N (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 3.0 μm), 3L3N (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 5.7 μm), 3L3 (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 8.0 μm), 2L3N (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle diameter 9.9 μm), 1110F (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 3.8 μm), 1050YP (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 0.94 μm), 1100YP (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 1.2 μm), 1200YP (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 3.4 μm), and 1400YP (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 5.2 μm).

[0045] The content of the micro copper particles may be more than 0 mass%, 5 mass% or more, 10 mass% or more, or 20 mass% or more, and 70 mass% or less, 50 mass% or less, or 40 mass% or less, based on the total mass of the metal particles, from the viewpoint that the above-mentioned effect by combining with the sub-micro copper particles is easily obtained. From the above viewpoint, the content of the micro copper particles may be more than 0 mass% and 70 mass% or less, 5 mass% or more and 50 mass% or less, 10 mass% or more and 40 mass% or less, or 20 mass% or more and 40 mass% or less, based on the total mass of the metal particles.

[0046] The copper particles may contain copper nanoparticles to the extent that the effects of the microcopper particles and submicrocopper particles described above are not impaired. Copper nanoparticles refer to copper particles having a particle size of less than 0.01 μm. From the viewpoint of making the sintered copper pillars denser and increasing the copper content, the content of the copper nanoparticles is preferably 30% by mass or less, more preferably 15% by mass or less, and even more preferably 0% by mass (i.e., no copper nanoparticles) based on the total mass of the metal particles.

[0047] [Metal particles other than copper particles] Examples of metal particles other than copper particles (other metal particles) include zinc, nickel, silver, gold, palladium, platinum, and the like. The volume average particle size of the other metal particles may be 0.01 μm or more and 10 μm or less, 0.01 μm or more and 5 μm or less, or 0.05 μm or more and 3 μm or less. From the viewpoint of obtaining sufficient bonding properties, the content of the other metal particles may be less than 20 mass%, 10 mass% or less, 5 mass% or less, or 0 mass% (i.e., not including copper nanoparticles) based on the total mass of the metal particles. The shape of the other metal particles is not particularly limited.

[0048] When the metal particles contain other metal particles, particularly when the metal particles contain metal particles having a metal species with a low solidification point, the sintering temperature can be lowered. Furthermore, since a sintered body in which multiple metals are dissolved or dispersed can be obtained, the mechanical properties of the sintered body, such as the yield stress and fatigue strength, can be improved, and the connection reliability can be improved. Furthermore, by adding multiple types of metal particles, the sintered body can have sufficient bonding strength to a specific adherend. In particular, when the bonding member is a microdevice, the die shear strength and connection reliability of the microdevice can be improved.

[0049] (Organic dispersion medium) The organic dispersion medium contains an organic dispersion medium (high boiling dispersion medium) having a boiling point of 280° C. or more at a ratio of more than 99% by mass based on the total mass of the organic dispersion medium. In other words, the content of an organic dispersion medium (low boiling dispersion medium) having a boiling point of less than 280° C. in the organic dispersion medium is less than 1% by mass based on the total mass of the organic dispersion medium. The organic dispersion medium may be composed of only a high boiling dispersion medium. The high boiling dispersion medium may be used alone or in combination.

[0050] The boiling point of the high-boiling dispersion medium is preferably 290°C or higher, more preferably 300°C or higher. A dispersion medium having such a boiling point is likely to remain in the pillar precursor up to the firing temperature of 150°C to 300°C, so that adhesion and flexibility are more likely to be maintained. In addition, by using a dispersion medium having such a boiling point, there is a tendency that the standing time (the time from the formation of the pillar precursor to the mounting of the joining member) during which stable formation of the joining by the sintered copper pillar is possible can be made longer. On the other hand, the boiling point of the high-boiling dispersion medium is preferably 450°C or lower, more preferably 400°C or lower. The dispersion medium is volatilized and removed by its vapor pressure even at a temperature below its boiling point, but when an organic dispersion medium having a boiling point of 450°C or lower is used, the volatilization speed does not become too slow at the sintering temperature of 150°C to 300°C, and sintering inhibition due to the remaining dispersion medium is less likely to occur.

[0051] It is preferable to select a high-boiling dispersion medium with a structure having a high affinity with the surface of metal particles in order to improve the dispersibility of the metal particles (e.g., copper particles such as submicro copper particles and micro copper particles). For example, when the metal particles are surface-treated with a surface treatment agent containing an alkyl group, it is preferable to select a dispersion medium having an alkyl group. As a combination of the surface treatment agent of the metal particles and the high-boiling dispersion medium, it is preferable that the surface treatment agent is an organic acid containing an alkyl group having 1 to 17 carbon atoms, and the high-boiling dispersion medium is a dispersion medium containing an alkyl group having 1 to 17 carbon atoms, it is more preferable that the surface treatment agent is an organic acid containing an alkyl group having 5 to 17 carbon atoms, and the high-boiling dispersion medium is a dispersion medium containing an alkyl group having 5 to 17 carbon atoms, and it is even more preferable that the surface treatment agent is an organic acid containing an alkyl group having 10 to 17 carbon atoms, and the high-boiling dispersion medium is a dispersion medium containing an alkyl group having 10 to 17 carbon atoms. According to the above combination, the metal particles can be dispersed well even when the content of the high-boiling dispersion medium is increased.

[0052] Specific examples of high-boiling dispersion media include isobornylcyclohexanol (MTPH, manufactured by Nippon Terpene Co., Ltd.), butyl stearate, Exepar BS (manufactured by Kao Corporation), stearyl stearate, Exepar SS (manufactured by Kao Corporation), 2-ethylhexyl stearate, Exepar EH-S (manufactured by Kao Corporation), isotridecyl stearate, Exepar TD-S (manufactured by Kao Corporation), isooctadecanol, Fine Oxocol 180 (manufactured by Nissan Chemical Industries, Ltd.), Fine Oxocol 180T (manufactured by Nissan Chemical Industries, Ltd.), 2-hexyldecanol, Fine Oxocol 1600 (manufactured by Nissan Chemical Industries, Ltd.), tributyrin, tetraethylene glycol, heptadecane, octadecane, nonadecane, eicosane, heneicosane, docosane, and methylheptadecanol. Examples of the isocyanate include butyl ether, tridecyl cyclohexane, tetradecyl cyclohexane, pentadecyl cyclohexane, hexadecyl cyclohexane, undecyl benzene, dodecyl benzene, tetradecyl benzene, tridecyl benzene, pentadecyl benzene, hexadecyl benzene, heptadecyl benzene, nonyl naphthalene, diphenylpropane, octyl octanoate, methyl myristate, ethyl myristate, methyl linoleate, methyl stearate, triethylene glycol bis(2-ethylhexanoic acid), tributyl citrate, pentylphenol, dibutyl sebacate, oleyl alcohol, cetyl alcohol, methoxyphenethyl alcohol, benzyl phenol, hexadecane nitrile, heptadecyl nitrile, benzyl benzoate, and cinmethylin.

[0053] The organic dispersion medium includes an organic dispersion medium having a freezing point of 20° C. or less (low freezing point dispersion medium). The low freezing point dispersion medium may be a high boiling point dispersion medium. That is, the boiling point of the low freezing point dispersion medium may be 280° C. or more. The freezing point of the low freezing point dispersion medium may be 15° C. or less, 10° C. or less, 5° C. or less, or 0° C. or less, from the viewpoint of improving printability and being more excellent in sinterability and bondability. The freezing point of the low freezing point dispersion medium may be -10° C. or more, -5° C. or more, 0° C. or more, 5° C. or more, or 10° C. or more. The low freezing point dispersion medium may be used alone or in combination of multiple types.

[0054] When the organic dispersion medium contains an organic dispersion medium having a freezing point of 10 to 20° C. as a low-freezing point dispersion medium, the printability, sinterability, and bondability tend to be better. From the viewpoint of obtaining such effects more significantly, the organic dispersion medium may contain two or more organic dispersion mediums having a freezing point of 10 to 20° C., and may contain an organic dispersion medium having a freezing point of 10 to 20° C. and an organic dispersion medium having a freezing point of 15° C. or lower (for example, an organic dispersion medium having a freezing point of 0° C. or lower).

[0055] Examples of low-freezing point dispersion media include 2-ethylhexyl stearate, isotridecyl stearate, isobornylcyclohexanol, octyl octanoate, 4-n-octylaniline, benzhydrylamine, isostearyl alcohol, isooctadecanol, 2-hexyldecanol, tetradecyl mercaptan, phenyl p-trisulfide, tributyrin, methyl myristate, ethyl myristate, methyl linoleate, triethylene glycol bis(2-ethylhexanoate), tributyl citrate, dibutyl sebacate, benzyl benzoate, dibutyl adipate, linoleate, ethyl ... Examples of suitable esters include methyl phthalate, dibutyl phthalate, bis(2-methoxyethyl) phthalate, ethoxycarbonylmethylethyl phthalate, tributyl O-acetylcitrate, dioctyl sebacate, dioctyl phthalate, tetrabutyltin, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, octadecane, tridecylbenzene, 2-methylheptadecane, 1-heptadecene, 1-phenylpentadecane, squalane, 4-bromodiphenyl ether, 1-iodonaphthalene, 1-bromo-4-methylnaphthalene, cresyl diphenyl phosphate, triphenyl phosphite, etc. Among these, from the viewpoint of excellent printability, sinterability, and bondability, at least one selected from the group consisting of 2-ethylhexyl stearate, isotridecyl stearate, isobornylcyclohexanol, and octyl octanoate is preferably used.

[0056] From the viewpoint of achieving superior printability, sinterability, and bondability, the organic dispersion medium may contain isotridecyl stearate and at least one selected from the group consisting of 2-ethylhexyl stearate, octyl octanoate, and isobornylcyclohexanol. In this case, the content of isotridecyl stearate may be 30% by mass or more, 40% by mass or more, or 50% by mass or more, and may be 70% by mass or less, 60% by mass or less, or 50% by mass or less, based on the total mass of the organic dispersion medium.

[0057] From the viewpoint of achieving superior printability, sinterability, and bondability, the organic dispersion medium may contain 2-ethylhexyl stearate and at least one selected from the group consisting of octyl octanoate, isotridecyl stearate, and isobornylcyclohexanol. In this case, the content of 2-ethylhexyl stearate may be 30% by mass or more, 40% by mass or more, or 50% by mass or more, and may be 70% by mass or less, 60% by mass or less, or 50% by mass or less, based on the total mass of the organic dispersion medium.

[0058] From the viewpoint of achieving superior printability, sinterability, and bondability, the organic dispersion medium may contain isobornylcyclohexanol and at least one selected from the group consisting of octyl octanoate, 2-ethylhexyl stearate, and isotridecyl stearate. In this case, the content of isobornylcyclohexanol may be 30% by mass or more, 40% by mass or more, or 50% by mass or more, and 70% by mass or less, 60% by mass or less, or 50% by mass or less, based on the total mass of the organic dispersion medium.

[0059] From the viewpoint of being more excellent in printability, sinterability and bondability, the organic dispersion medium may contain at least one selected from the group consisting of isobornylcyclohexanol, 2-ethylhexyl stearate and isotridecyl stearate, or may contain octyl octanoate and at least one selected from the group consisting of isobornylcyclohexanol, 2-ethylhexyl stearate and isotridecyl stearate. In this case, the content of octyl octanoate may be 30% by mass or more, 40% by mass or more, or 50% by mass or more, and may be 70% by mass or less, 60% by mass or less, or 50% by mass or less, based on the total mass of the organic dispersion medium.

[0060] From the viewpoint of superior printability, sinterability and bondability, the content of the low-freezing point dispersion medium is preferably more than 50 mass%, more preferably 60 mass% or more, and even more preferably 70 mass% or more, based on the total mass of the organic dispersion medium. The content of the low-freezing point dispersion medium may be 100 mass% or less, 90 mass% or less, or 80 mass% or less, based on the total mass of the organic dispersion medium.

[0061] The content of the organic dispersion medium may be 1 mass% or more, 2 mass% or more, 3 mass% or more, or 4 mass% or more based on the total mass of the copper paste from the viewpoint of adjusting the viscosity of the copper paste to a more appropriate value, and the content of the organic dispersion medium may be 20 mass% or less, 10 mass% or less, or 5 mass% or less based on the total mass of the copper paste from the viewpoint of further improving the sinterability of the copper particles.

[0062] The type of organic dispersion medium contained in the copper paste can be analyzed, for example, by gas chromatography-mass spectrometry of high-temperature desorbed gas and TOF-SIMS. As another analytical method, the supernatant obtained by separating the particle components by centrifugation may be identified by conventional organic analysis, for example, FT-IR, NMR, liquid chromatography, or a combination of these. The ratio of the types of organic dispersion medium can be quantified by liquid chromatography, NMR, etc.

[0063] (Components other than metal particles and organic dispersion medium) The copper paste may further contain components other than the metal particles and the organic dispersion medium, such as a flexibility-imparting component such as a thermally decomposable resin, a filler, a dispersant, and a flux.

[0064] The thermally decomposable resin is preferably a non-crystalline polymer capable of exhibiting adhesiveness or tackiness for the purpose of temporarily fixing the pillar precursor to the bonding member, which is the adherend, from after the pillar precursor is formed to after the firing. In addition, the thermally decomposable resin is preferably thermally decomposable at the sintering temperature without leaving any residue.

[0065] The thermal decomposition temperature of the thermally decomposable resin is preferably 300° C. or lower, and more preferably 250° C. or lower. The thermal decomposition temperature of the thermally decomposable resin is the decomposition initiation temperature of the thermally decomposable resin, which is the temperature at which the resin starts to lose 5% weight in TG / DTA measurement. However, this temperature does not mean the decomposition initiation temperature in an oxidizing atmosphere such as air, but in a reducing gas atmosphere containing hydrogen or formic acid, or in an inert gas atmosphere from which oxygen has been removed.

[0066] The less the residue after pyrolysis of the pyrolyzable resin, the better since it hinders the sintering of the copper particles. Usually, the amount of residue at the sintering temperature is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 2% by mass or less, based on the mass of the resin before pyrolysis. The amount of residue after pyrolysis of the pyrolyzable resin can be measured as the weight change amount after holding at the sintering temperature for the sintering time by TG / DTA of the pyrolyzable resin in an inert gas (nitrogen or argon) containing 3 to 5% by mass of hydrogen. Note that TG / DTA measurement in air is not preferred because the amount of residue is smaller than that in a reducing gas atmosphere due to the progress of oxidative decomposition.

[0067] The thermally decomposable resin has, for example, solubility in the organic dispersion medium described above. Examples of the thermally decomposable resin having solubility in the organic dispersion medium and the desired properties described above include polycarbonate, polymethacrylic acid, polymethacrylic acid ester, and polyester.

[0068] The content of the thermally decomposable resin may be 25% by mass or less, 15% by mass or less, 5% by mass or less, or 3% by mass or less based on the total mass of the copper paste. If the purpose is to form a sintered copper pillar, the thermally decomposable resin does not need to be blended. On the other hand, from the viewpoint of increasing the proportion of the flexibility-imparting component contained in the entire dispersion medium and reducing the progress of drying, the content of the thermally decomposable resin may be 5% by mass or more based on the total mass of the copper paste.

[0069] The viscosity of the copper paste may be a viscosity suitable for the printing and coating method for forming the pillar precursor. From the viewpoint of facilitating the formation of the pillar precursor by various printing methods described later, the viscosity of the copper paste at 25°C may be 50 Pa·s or more and 2000 Pa·s or less, 100 Pa·s or more and 1750 Pa·s or less, or 200 Pa·s or more and 1500 Pa·s or less. The viscosity of the copper paste means a value measured by an E-type viscometer at 25°C and a rotation speed of 0.5 rpm. As the E-type viscometer, for example, a VISCOMETER-TV33 type viscometer manufactured by Toki Sangyo Co., Ltd. can be used. As a measuring tool for the cone rotor, for example, 3°×R14, SPP can be applied.

[0070] The thixotropy index (hereinafter also referred to as "TI value") of the copper paste may be 2.0 or more and 20 or less, 3.0 or more and 15 or less, or 4.0 or more and 10 or less. When the TI value of the copper paste is within this range, the viscosity of the copper paste is reduced by shear force, so that the copper paste can be easily printed by stirring it manually or with a stirrer (for example, a rotation-revolution type stirrer (Planetary Vacuum Mixer ARV-310, manufactured by Thinky Corporation) before printing, and the viscosity of the copper paste is restored by leaving it to stand after it is attached to the joining member, so that excessive wetting and spreading of the printed matter can be suppressed. The TI value of the copper paste is calculated by dividing the viscosity measured by μ using an E-type viscometer at 25°C and a rotation speed of 0.5 rpm. 0.5The viscosity measured by an E-type viscometer at 25°C and a rotation speed of 5 rpm is μ5, and the value is calculated by the following formula. TI value = μ 0.5 / μ5

[0071] <Method of preparing copper paste> The copper paste can be prepared by mixing the above-mentioned metal particles, the organic dispersion medium, and, if necessary, any components such as a flexibility-imparting component. Specifically, for example, the copper paste may be prepared by adding sub-micro copper particles, micro copper particles, and, if necessary, other metal particles and any additives to a mixed liquid (solution) of the flexibility-imparting component and the organic dispersion medium, and performing a dispersion treatment. In addition, for example, the copper paste may be prepared by mixing a mixed liquid (solution) of the flexibility-imparting component and the organic dispersion medium, a mixed liquid (dispersion) of copper particles and the organic dispersion medium, and, if necessary, other metal particles and any additives.

[0072] When the copper particles include submicro copper particles and micro copper particles, first, the submicro copper particles and, if necessary, a dispersant are added to an organic dispersion medium or a flexibility-imparting component, and then the mixture is dispersed. Then, micro copper particles and, if necessary, other metal particles are added and dispersed. The dispersion method and dispersion conditions suitable for the dispersion of submicro copper particles and micro copper particles may differ. Generally, submicro copper particles require a stronger dispersion than micro copper particles, while micro copper particles are easily dispersed and a low dispersion is sufficient, and micro copper particles are deformed by strong dispersion. By following the above procedure, the dispersibility is improved, and the performance of the copper paste can be further improved. The dispersion may be classified to remove aggregates.

[0073] In this preparation method, a stirring process may be performed after mixing the components. The copper paste may be classified to adjust the maximum particle size of the dispersion. In this case, the maximum particle size of the dispersion can be 20 μm or less, or 10 μm or less.

[0074] The dispersion treatment can be carried out using a dispersing machine or agitating machine, examples of which include an Ishikawa type agitating machine, a Silverson agitating machine, a cavitation agitating machine, a rotation-revolution type agitating machine, an ultra-thin film high-speed rotary dispersing machine, an ultrasonic dispersing machine, a Raikai machine, a twin-screw kneading machine, a bead mill, a ball mill, a triple roll mill, a homomixer, a planetary mixer, an ultra-high pressure type dispersing machine, and a thin layer shear dispersing machine.

[0075] The stirring treatment can be carried out using a stirrer, such as an Ishikawa stirrer, a rotation-revolution type stirrer, a Raikai mixer, a twin-screw kneader, a three-roll mill, or a planetary mixer.

[0076] The classification operation can be carried out, for example, by using filtration, natural sedimentation, centrifugation, etc. Examples of filters for filtration include water combs, metal meshes, metal filters, nylon meshes, etc.

[0077] <zygote> 1, a bonded body 10 of one embodiment includes a first member 1, a second member 2, and a sintered copper pillar 3 that bonds the first member 1 and the second member 2. The sintered copper pillar 3 is made of, for example, a sintered body of the above-mentioned copper paste.

[0078] The lower and upper surfaces of the sintered copper pillar form the bonding surfaces with the first and second members, respectively, and the two are bonded together by metallic bonding. The formation of such metallic bonding allows the bonded body to have low electrical resistance and be firmly bonded.

[0079] Examples of the first member 1 and the second member 2 include an active or passive electronic device, a wiring board on which an electronic device is mounted, and a package having an electronic device and a rewiring layer provided on the electronic device.

[0080] Examples of electronic devices include coils, capacitors, SAW filters, power ICs, logic chips, memory chips, sensors, piezoelectric elements, transistors, and diodes.

[0081] Examples of wiring boards include mounting substrates, lead frames such as copper lead frames, ceramic substrates, resin molded products having printed metal wiring such as MIDs (Molded Interconnect Devices), and packages having rewiring layers.

[0082] One of the first member 1 and the second member 2 may be an active or passive electronic device, and the other may be a wiring board on which an electronic device is mounted, in which case highly reliable electronic device mounting is possible.

[0083] Furthermore, both the first member 1 and the second member 2 may be packages having an electronic device and a redistribution layer provided on the electronic device, which enables highly reliable package-on-package mounting.

[0084] The first member 1 and / or the second member 2 may contain one or more metals selected from the group consisting of copper, nickel, silver, platinum, gold, and palladium on the bonding surface with the sintered copper pillar 3. Specifically, for example, a metal film or sintered metal layer containing one or more metals selected from the group consisting of copper, nickel, silver, platinum, gold, and palladium may be provided on the first member 1 and / or the second member 2. When the bonding surface contains these metals, it becomes possible to reduce and remove the oxide film on the surface at a sintering temperature of 300° C. or less in a reducing gas atmosphere such as hydrogen or formic acid. Therefore, the bonded body 10 can have high bonding strength due to the metal bond between the exposed metal surface of the member and the sintered copper pillar.

[0085] The sintered copper pillar 3 preferably has a copper content of 96 mass% or more, more preferably 96.5 mass% or more, and even more preferably 97 mass% or more, based on the total mass of the components constituting the sintered copper pillar (excluding carbon, oxygen, and nitrogen). Note that the above carbon, oxygen, and nitrogen are components that may be unintentionally contained in the sintered copper pillar due to filling with an underfill or a sealing material during mounting.

[0086] The sintered copper pillar having the copper content in the above range can be easily formed by printing and sintering the copper paste described above. In addition, when the copper content in the sintered copper pillar is in the above range, it is advantageous in terms of ensuring the bonding strength and suppressing electromigration. In addition, when the bonding surface contains copper, the bonding is made of the same metal, so it is easy to suppress the occurrence of Kirkendall voids, and a bonded body with even better connection reliability can be obtained.

[0087] From the viewpoint of thermal conductivity and electrical conductivity, the volume ratio of copper in the sintered copper pillar 3 is preferably 50 volume % or more, more preferably 60 volume % or more, and even more preferably 70 volume % or more. The larger the volume ratio of copper in the sintered copper pillar 3, the higher the thermal conductivity and electrical conductivity of the sintered copper pillar 3. The volume ratio of copper in the sintered copper pillar 3 can be obtained from an SEM image of the cross section of the sintered copper pillar. In this specification, the parts of the sintered copper pillar other than copper are expressed as voids. When a resin component such as a filler or underfill is contained in the void, the volume of the component is also included in the volume of the void.

[0088] The height H of the sintered copper pillar 3 may be 5 to 200 μm, 10 to 150 μm, or 20 to 100 μm. Here, the height of the sintered copper pillar 3 refers to the shortest distance between the bonding surface of the sintered copper pillar 3 with the first member 1 and the bonding surface with the second member 2.

[0089] The width (diameter) W of the sintered copper pillar 3 may be 10 to 500 μm, 25 to 300 μm, or 50 to 150 μm. Here, the width (diameter) of the sintered copper pillar 3 refers to the minimum diameter of a cross section perpendicular to the height direction of the sintered copper pillar 3 (the direction in which the pillar extends).

[0090] The sintered copper pillar 3 may have a ratio (H / W) of the height H to the width W (sometimes referred to as the "cross-sectional aspect ratio of the sintered copper pillar") of 0.01 to 4.0, 0.1 to 2.5, or 0.15 to 2.0.

[0091] The height H and width W can be determined from an SEM image of the cross section of the sintered copper pillar.

[0092] The shear strength at the interface between the sintered copper pillar 3 and the first member and / or the second member (the shear strength between the joining surface of the sintered copper pillar 3 and the joining surface of the first member and / or the second member) can be 4 MPa or more, may be 10 MPa or more, or may be 20 MPa or more. In this case, the joining surface of the first member and / or the second member may contain the above-mentioned metal. For example, the joining surface of the first member and / or the second member may be the surface of a metal layer containing the above-mentioned metal.

[0093] The shear strength can be calculated, for example, by using a bonding strength testing device to push the sintered copper pillar horizontally at a constant speed with the tool of the device, and dividing the maximum strength at which the bonding surface between the sintered copper pillar and the component peels off by the cross-sectional area of ​​the pillar.

[0094] The manufacturing method of the bonded body 10 described above includes a step of forming the copper paste into a pillar shape on the first member 1, mounting the second member 2, and providing a pillar precursor between the first member 1 and the second member 2 (hereinafter also referred to as the "first step"), and a step of forming a sintered copper pillar 3 by sintering the pillar precursor (hereinafter also referred to as the "second step"). The method will be described in detail below with reference to Figs. 2 and 3.

[0095] (First step) In the first step, first, as shown in FIG. 2, for example, copper paste 3a is formed into pillar shapes on a first member 1 by printing or the like.

[0096] Examples of a printing method for the copper paste that can be used include screen printing, transfer printing, offset printing, jet printing, a dispenser, a jet dispenser, a needle dispenser, a comma coater, a slit coater, a die coater, a gravure coater, a slit coat, letterpress printing, intaglio printing, gravure printing, stencil printing, soft lithography, a bar coat, an applicator, a particle deposition method, a spray coater, a spin coater, a dip coater, and electrochemical coating.

[0097] From the viewpoints of simple manufacturing process, easy maintenance of shape stability, and easy thick-film printing, it is preferable to form the copper paste into a pillar shape by screen printing or stencil printing. In screen printing and stencil printing, for example, first, a metal mask 4 is placed on the first member 1 (FIG. 2(a)). Next, copper paste 3a is placed on the first member 1 and the metal mask 4 (FIG. 2(b)). Next, the copper paste 3a is spread using a squeegee 5, and the copper paste 3a is filled into the holes of the metal mask 4 (FIG. 2(c)). In this way, the copper paste 3b formed into a pillar shape is formed on the first member 1 (FIG. 3(a)).

[0098] The via diameter of the metal mask used for screen printing or stencil printing may be 30 μm or more and 200 μm or less, or 50 μm or more and 100 μm or less. The holes may be arranged in a lattice pattern. The pitch interval may be 1 μm or more and 500 μm or less. The squeegee angle may be 10° or more and 90° or less, or 45° or more and 70° or less.

[0099] The printing height H1 may be 5 μm or more and 500 μm or less, or may be 10 μm or more and 200 μm or less. In addition, the wetting spread W1 from the pillar end after printing may be 100 μm or less, or may be 50 μm or less.

[0100] Next, as shown in Fig. 3, for example, the second member 2 is mounted on the first member (on the copper paste 3b formed in a pillar shape), and a pillar precursor 3c is provided between the first member 1 and the second member 2. Specifically, as shown in Fig. 3(b), for example, the second member 2 is pushed in from above the copper paste 3b formed in a pillar shape, so that the second member 2 is mounted on the first member. In this way, the pillar precursor 3c is provided between the first member 1 and the second member 2.

[0101] The method for mounting the second member 2 is not particularly limited, but for example, when the first member 1 and the second member 2 are a microdevice and a substrate, a method using, for example, a chip mounter, a flip chip bonder, or a carbon or ceramic positioning jig may be used.

[0102] The indentation depth (H1-H2) when the second component 2 is mounted may be 500 μm or less, 100 μm or less, or 50 μm or less from the top of the pillar-shaped copper paste. H2 is set in consideration of the height of the sintered copper pillar or pillar precursor to be formed.

[0103] (Second step) In the second step, the pillar precursor 3c disposed between the first member 1 and the second member 2 is sintered. As a result, the sintered copper pillar 3 is formed, and the first member 1 and the second member 2 are joined by the sintered copper pillar 3, thereby obtaining a joined body 10 shown in FIG. 3(c).

[0104] The pillar precursor 3c may be dried appropriately from the viewpoint of suppressing flow and generation of voids during sintering. The gas atmosphere during drying may be air, an oxygen-free atmosphere such as nitrogen or a rare gas, or a reducing gas atmosphere such as hydrogen or formic acid. The drying method may be drying by leaving at room temperature, heating, or drying under reduced pressure. For heating or drying under reduced pressure, for example, a hot plate, a hot air dryer, a hot air heating furnace, a nitrogen dryer, an infrared dryer, an infrared heating furnace, a far-infrared heating furnace, a microwave heating device, a laser heating device, an electromagnetic heating device, a heater heating device, a steam heating furnace, a hot plate pressing device, or the like can be used. The drying temperature and time may be appropriately adjusted according to the type and amount of the organic dispersion medium and the flexibility-imparting component used. The drying temperature and time can be, for example, 50°C or higher and 180°C or lower for 30 seconds to 120 minutes.

[0105] The pillar precursor 3c can be sintered by a heat treatment, for example, a hot plate, a hot air dryer, a hot air heating furnace, a nitrogen dryer, an infrared dryer, an infrared heating furnace, a far-infrared heating furnace, a microwave heating device, a laser heating device, an electromagnetic heating device, a heater heating device, a steam heating furnace, or the like can be used for the heat treatment.

[0106] The gas atmosphere during sintering may be a reducing gas atmosphere from the viewpoint of removing copper particles contained in the pillar precursor 3c and surface oxides on the deposition surface. Examples of the reducing gas atmosphere include a pure hydrogen gas atmosphere, a mixed gas atmosphere of hydrogen and nitrogen such as forming gas, a nitrogen atmosphere containing formic acid gas, a mixed gas atmosphere of hydrogen and a rare gas, and a rare gas atmosphere containing formic acid gas.

[0107] When the diameter of the pillar precursor 3c is small (especially when it is 200 μm or less), the formic acid penetrates into the interior of the pillar precursor 3c, making it easier to reduce the copper particles, and the copper particles can be sufficiently sintered in a reducing gas atmosphere containing formic acid gas. In this case, it is possible to sinter using a formic acid reflow furnace, and the degree of sintering can be improved efficiently.

[0108] The maximum temperature reached during the heat treatment may be 150° C. or higher and 300° C. or lower, 170° C. or higher and 250° C. or lower, or 200° C. or higher and 250° C. or lower, from the viewpoints of sufficiently advancing sintering, reducing thermal damage to members such as the microdevice and the substrate, and improving the yield. If the maximum temperature reached is 150° C. or higher, sintering tends to proceed sufficiently even if the maximum temperature is held for 60 minutes or less.

[0109] The time for which the maximum temperature is maintained may be from 1 minute to 60 minutes, from the viewpoint of being able to sufficiently remove the organic dispersion medium and the flexibility-imparting component, to sufficiently advance sintering, and to improve the yield, or may be from 1 minute to less than 40 minutes, or may be from 1 minute to less than 30 minutes.

[0110] Although one embodiment of the bonded body and the manufacturing method thereof have been described above, the present invention is not limited to the above embodiment.

[0111] For example, the method for manufacturing the bonded body may further include a step of filling the periphery of the sintered copper pillar with resin, in which case, as shown in FIG. 4, a bonded body 20 is obtained in which a sealing material 6 is provided between a first member 1 and a second member 2.

[0112] As the sealing material, from the viewpoint of protecting the joining portion from heat, moisture and impact and further improving the connection reliability, a compression molding sealing material, a liquid sealing material, a transfer molding sealing material, an underfill sealing material, etc. can be used. EXAMPLES

[0113] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0114] Example 1 The copper paste was prepared, a bonded body was produced and evaluated, and a bonding member with pillars was produced and evaluated by the following methods.

[0115] [Preparation of copper paste] Octyl octanoate (organic dispersion medium, Sigma-Aldrich Japan GK, boiling point: 307°C, freezing point: 18°C) 0.07 g, 2-ethylhexyl stearate (organic dispersion medium, Kao Corporation, boiling point: 340°C, freezing point: 9°C) 0.07 g, and CH-0200 (submicro copper particles, Mitsui Kinzoku Co., Ltd., product name, 50% volume average particle size: 0.36 μm, surface treatment agent: lauric acid) and octyl octanoate (dispersion medium, Sigma-Aldrich Japan GK) previously prepared were mixed. A slurry mixture of 16.18 g of CH-200 (manufactured by GK) and 2-ethylhexyl stearate (organic dispersion medium, manufactured by Kao Corporation) (CH-200:octyl octanoate:2-ethylhexyl stearate=90:5:5, mass ratio) and 3.52 g of MA-025KFD (flake-shaped micro copper particles, product name, manufactured by Fukuda Metal Foil & Powder Co., Ltd., 50% volume average particle size: 5.9 μm) were kneaded in an agate mortar until no dry powder remained, and the mixed liquid was transferred to a plastic bottle.

[0116] The sealed plastic bottles were mixed in a planetary vacuum mixer (ARV-310, manufactured by Thinky Corporation) for 2000 min. -1 The mixture was stirred at 2000 rpm for 2 minutes to obtain a copper paste.

[0117] [Printability evaluation] First, a stainless steel metal mask (thickness: 70 microns) with circular openings was placed on a silicon wafer (size: 6 inches), and copper paste was applied by stencil printing using a metal squeegee. In this way, pillars (pillar-shaped copper paste) were placed on the silicon wafer. The opening diameter of the metal mask was 150 microns. Next, the number of pillars placed on the silicon wafer was confirmed using a digital microscope (VHX-6000, manufactured by Keyence Corporation). The printability was evaluated according to the following criteria. The results are shown in Tables 1 and 2. ○: The ratio of the number of formed pillars to the total (mask aperture number) is 80% or more and 100% or less. △: The ratio of the number of formed pillars to the total (mask aperture number) is 50% or more and less than 80%. ×: The ratio of the number of formed pillars to the total (mask aperture number) is 0% or more and less than 50%.

[0118] [Preparation of junction] The copper paste obtained above was used to form a bonded body by the following method. A stainless steel metal mask (thickness: 70 μm) with φ150 μm openings arranged in a grid pattern with a pitch of 500 μm was placed on a copper plate (size: 15 mm × 20 mm, thickness: 3 mm) as a first member, and the copper paste was applied by stencil printing using a metal squeegee. After applying the copper paste, a Cu-plated Si chip (size: 3 mm × 3 mm, thickness: 0.15 mm) as a second member was mounted on the pillar-shaped copper paste provided on the substrate using a flip chip bonder (T-3000-TC-3, manufactured by Dr. Tresky). Then, these laminates (copper plate / pillar precursor / Si chip) were placed in a sintering furnace (reducing gas atmosphere of 10% hydrogen / 90% nitrogen), heated to 225 ° C over 30 minutes, and held at 225 ° C for 60 minutes. Then, the bonded body was obtained by cooling to 50 ° C or less with water cooling.

[0119] [Joint evaluation] Ultrasonic inspection of the joints was carried out using an ultrasonic scanning device (IS-300, manufactured by Insight). The frequency of the probe was 35 MHz. In the image obtained by ultrasonic inspection, the parts where the pillars were joined that were successfully joined are displayed in black. The number of parts where the joints were successfully joined (joints that appear in black) in the obtained image was counted as the number of joints, and the joinability was evaluated based on the ratio of the number of joints to the total (joints) using the following criteria. The results are shown in Tables 1 and 2. ○: The percentage of joints is between 80% and 100% of the total (joints). △: The ratio of the number of joints is 50% or more but less than 80% of the total (joints). ×: The percentage of joints is 0% or more and less than 50% of the total (joints).

[0120] [Sinterability evaluation] The bonded body was placed in a plastic cup, and epoxy resin (Epomount, Refine Tech Co., Ltd.) was poured around it until the bonded body was buried. The cup was then placed in a vacuum desiccator and decompressed for 1 minute to degas it. The epoxy resin was then left at room temperature (25°C) for 10 hours to harden. Next, the bonded section was cut using a Refine Saw Excel (RCB-961, Refine Tech Co., Ltd.) equipped with a diamond cutting wheel (11-304, Refine Tech Co., Ltd.). The cross section was then polished using a polishing device (Refine Polisher HV, Refine Tech Co., Ltd.) equipped with waterproof abrasive paper (carbon paper, Refine Tech Co., Ltd.). The CP processing device (IM4000, Hitachi Ltd.) was used with an accelerating voltage of 6 kV and an argon gas flow rate of 0.07 to 0.1 cm. 3 / min, and processing time 20 minutes. Next, platinum was sputtered to a thickness of 10 nm using a sputtering device (ION SPUTTER, Hitachi High-Technologies Corporation) to prepare a sample for SEM observation. The cross section of the joint was observed at various magnifications with an SEM device (ESEM XL30, Philips) at an applied voltage of 10 kV, and the sinterability was evaluated according to the following criteria. The results are shown in Tables 1 and 2. ○: The number of voids and cracks in the sintered copper pillar is less than 10 △: The number of voids and cracks in the sintered copper pillar is 10 to 50 ×: The number of voids and cracks in the sintered copper pillar is 50 or more.

[0121] Example 2 A copper paste was prepared in the same manner as in Example 1, except that the amounts of octyl octanoate and 2-ethylhexyl stearate used were adjusted so that the compounding ratio (mass ratio) of octyl octanoate to 2-ethylhexyl stearate in the copper paste and the slurry mixture was 3:7. In addition, printability, sinterability, and bondability were evaluated in the same manner as in Example 1, except that the obtained copper paste was used.

[0122] Example 3 A copper paste was prepared in the same manner as in Example 2, except that isotridecyl stearate (organic dispersion medium, manufactured by Kao Corporation, boiling point: 489.84°C, solidification point: 12°C) was used instead of 2-ethylhexyl stearate. In addition, printability, sinterability, and bondability were evaluated in the same manner as in Example 1, except that the obtained copper paste was used.

[0123] Example 4 A copper paste was prepared in the same manner as in Example 3, except that the amounts of 2-ethylhexyl stearate and isotridecyl stearate used were adjusted so that the compounding ratio (mass ratio) of 2-ethylhexyl stearate to isotridecyl stearate in the copper paste and the slurry mixture was 4:6. In addition, printability, sinterability, and bondability were evaluated in the same manner as in Example 1, except that the obtained copper paste was used.

[0124] Example 5 A copper paste was prepared in the same manner as in Example 1, except that isobornylcyclohexanol (Tersolve MTPH, manufactured by Nippon Terpene Chemical Co., Ltd., boiling point: 308°C, freezing point: -6.2°C) was used as the organic dispersion medium instead of octyl octanoate. In addition, printability, sinterability, and bondability were evaluated in the same manner as in Example 1, except that the obtained copper paste was used.

[0125] Example 6 A copper paste was prepared in the same manner as in Example 5, except that isotridecyl stearate was used as the organic dispersion medium instead of 2-ethylhexyl stearate. In addition, printability, sinterability, and bondability were evaluated in the same manner as in Example 1, except that the obtained copper paste was used.

[0126] Example 7 A copper paste was prepared in the same manner as in Example 1, except that butyl stearate (organic dispersion medium, manufactured by FUJIFILM Wako Co., Ltd., boiling point: 343°C, solidification point: 25°C) was used instead of 2-ethylhexyl stearate, and the amounts of 2-ethylhexyl stearate and isotridecyl stearate used were adjusted so that the compounding ratio (mass ratio) of octyl octanoate to butyl stearate in the copper paste and the slurry mixture was 9:1. In addition, printability, sinterability, and bondability were evaluated in the same manner as in Example 1, except that the obtained copper paste was used.

[0127] Comparative Example 1 A copper paste was prepared in the same manner as in Example 2, except that dihydroterpineol (organic dispersion medium, manufactured by Nippon Terpene Chemical Co., Ltd., boiling point: 220°C) was used instead of 2-ethylhexyl stearate. In addition, printability, sinterability, and bondability were evaluated in the same manner as in Example 1, except that the obtained copper paste was used.

[0128] [Table 1]

[0129] [Table 2] [Explanation of symbols]

[0130] 1...first member, 2...second member, 3...sintered copper pillar, 3a...copper paste, 4...metal mask, 5...squeegee, 10, 20...joint body.

Claims

1. A copper paste for forming a sintered copper pillar that bonds components together, Contains metal particles and an organic dispersion medium, the metal particles include copper particles, The organic dispersion medium contains a high-boiling point dispersion medium having a boiling point of 280° C. or more in a proportion of more than 99 mass% based on the total mass of the organic dispersion medium, and contains a low-freezing point dispersion medium having a freezing point of 20° C. or less; The copper paste for forming a sintered copper pillar, wherein the low-freezing point dispersion medium includes an organic dispersion medium having a freezing point of 10 to 20°C and an organic dispersion medium having a freezing point of 15°C or lower.

2. The copper paste according to claim 1, wherein the content of the organic dispersion medium is 1 to 20 mass% based on the total mass of the copper paste.

3. The copper paste according to claim 1 or 2, wherein the content of the low-freezing point dispersion medium is 50 mass% or more based on the total mass of the organic dispersion medium.

4. The metal particles contain submicro copper particles having a volume average particle size of 0.01 μm or more and less than 0.8 μm in a ratio of 30 to 100 mass% based on the total mass of the metal particles. Copper paste according to any one of claims 1 to 3.

5. The metal particles contain micro copper particles having a volume average particle size of 0.8 μm or more and 50 μm or less, based on the total mass of the metal particles, in a ratio of more than 0 mass% to 70 mass% or less. The copper paste according to any one of claims 1 to 4.

6. A copper paste described in any one of claims 1 to 5, wherein the organic dispersion medium comprises isotridecyl stearate and at least one selected from the group consisting of 2-ethylhexyl stearate, octyl octanoate, and isobornylcyclohexanol.

7. The copper paste according to any one of claims 1 to 5, wherein the organic dispersion medium comprises 2-ethylhexyl stearate and at least one selected from the group consisting of octyl octanoate, isotridecyl stearate, and isobornyl cyclohexanol.

8. A method for manufacturing a joined body including a first member, a second member, and a sintered copper pillar joining the first member and the second member, comprising the steps of: A step of forming the copper paste according to any one of claims 1 to 7 into a pillar shape on the first member, mounting the second member, and providing a pillar precursor between the first member and the second member; and forming the sintered copper pillar by sintering the pillar precursor.

Citation Information

Patent Citations

  • Method for electrical coupling and electric coupling arrangement

    US20160351529A1

  • Copper paste for pressureless bonding, bonded body and semiconductor device

    WO2018131095A1